Nanocrystalline powders in the A12O3-ZrO2-CeO2- Y2O3 system for high-performance ceramics - Shevchenko, A. V.; Tsukrenko, V. V.; Dudnik, E. V.; Ruban, A. K. (Видавництво Львівської політехніки, 2012)
X-ray diffraction, BET measurements, scanning electron and optical microscopy were used to analyze the properties variation of hydrothermal nanocrystalline powder with a composition 90 wt% Al2O3-10 wt% ZrO2 (CeO2, Y2O3) after thermal treatment in the temperature range 400-1300 °С. The composition of the ZrO2-based solid solution was (mol %) 90ZrO2–8CeO2–2Y2O3. It was found that a-Al2O3 is formed at 850 °С. Phase transformation F-ZrO2 Т-ZrO2 occurred at 1000 °С. Produced powder was sintered at 1300 °С. The present investigation demonstrates that heat treatment of composite nanocrystalline powders gives rise to complex processes. Understanding of such processes makes it possible to optimize conditions for fabrication of advanced ceramics with tailored properties.
Keywords: nanocrystalline powder; phase transformation; a- Al2O3; specific surface area; Al2O3-ZrO2-CeO2-Y2O3 system